2019
DOI: 10.1109/access.2019.2936458
|View full text |Cite
|
Sign up to set email alerts
|

A Compact-Size Wideband Optically-Transparent Water Patch Antenna Incorporating an Annular Water Ring

Abstract: A wideband optically-transparent water patch antenna with a compact size is proposed. Both the water patch and the water ground plane are made of distilled water to realize the highly optical transparency. Particularly, by simply incorporating an annular water ring under the water patch, the center frequency can be reduced from 2.3 GHz to 1.95 GHz, while the corresponding size of the water patch can be reduced by 28%. Both the simulation and the measurement are carried out for verification. The measured result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…For instance, although ITO is commonly used, it is costly and brittle due to its rare-earth indium component [27], [30], and (6) Materials that have not been examined in light of design and materials loss [32]. Referring to the application for microwave frequencies, the addition of dense dielectric patch antenna (DDPA) can be applied to create patch antennas made of novel materials, in order to focus on the different challenges of complex wireless communications in future [73].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, although ITO is commonly used, it is costly and brittle due to its rare-earth indium component [27], [30], and (6) Materials that have not been examined in light of design and materials loss [32]. Referring to the application for microwave frequencies, the addition of dense dielectric patch antenna (DDPA) can be applied to create patch antennas made of novel materials, in order to focus on the different challenges of complex wireless communications in future [73].…”
Section: Methodsmentioning
confidence: 99%
“…Since the water represents 100% optically transparent material with very low material costs, transparent antennas are designed in contrast to other clear materials, such as transparent oxide conduction or transparent film. An optically transparent water patch antenna, consisting of the patch and ground plane, was proposed as Optically Transparent Antennas using plexiglass substrate with distilled water, for many promising applications in future transparent electronics designs and flexible electronics [71] , or for many practical applications [72] , and proposed as Compact and Transparent Antennas using plexiglass substrate with distilled water for ultra-wideband (UWB) [73] . Three articles (3.70%) had assessed liquid antennas (water) in light of transparent antenna, and two type of study (Optically Transparent Antennas, Compact and Transparent Antennas) to identify or to evaluate transparent antenna approaches.…”
Section: Watermentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the usable frequency band can be shifted by changing the height of the ground. In a follow up work [67], the authors modified the previous design by adding an annular water ring around the disk-loaded probe. This addition helped to reduce the size of the antenna (lower operating bandwidth) by effectively introducing an additional shunt capacitance between the patch and the ground.…”
Section: Antenna Geometry Variationsmentioning
confidence: 99%
“…Beside, many investigations of transparent antennas are focused on visible light. [6][7][8] IR transparent antennas, particularly for IR wavelengths with in the midwavelength (3-5 μm) range, have received less attention.…”
Section: Introductionmentioning
confidence: 99%